1871 Tex. Laws 25, ch. 34, § 3 - (:unkn) unknown (My University, 1871)
Prohibited carry of pistol, other firearm, dirk, dagger, slung-shot, sword-cane, spear, brass knuckles, Bowie-knife, any other knife for offense or defense in public assemblies for education or amusement, ball rooms, social parties, elections, locations for muster. Violators guilty of a misdemeanor punishable by fine no less than fifty but not more than five hundred dollars and forfeiture of the weapon. Subsequent violations shall also be jailed for no more than ninety days.
Keywords: CARRY - CERTAIN PUBLIC PLACES